The passage from infans to speaker and the hypothesis of a signifying function - Nunes, Paula Ávila (2023)
The intention is to articulate what Flores (2019) proposes regarding the transition from infans to speaker, with the author's later theorization in 2022 concerning the major functions of humans in language. To do so, reference is made to Giorgio Agamben's work "Infancy and History," aligning his proposition of the language being divided in langue and discourse with Benveniste's ideas about the two universes of meaning, the semiotic and the semantic. This articulation leads us to the hypothesis that there is what we can call a signifying function in human language, defending it conceptually and operationally as a fundamental element in this transition.